Contour Error Analysis Of Precise Positioning For Ball Screw Driven Stage Using Friction Model Feedforward - Rafan, Nur Aidawaty; Jamaludin, Zamberi; Chiew, Tsung Heng; Abdullah, Lokman; Maslan, Mohd Nazmin (2014)
This paper presents contouring error analysis using various classical feedforward controllers. A circular motion is performed using an XY positioning stage with specified amplitude and velocities. This study applied single Static friction model, Generalized Maxwell Slip (GMS) model and combination of both models together with feedforward Proportional-Integral-Derivative (PID) controller. Contour error in term of quadrant glitch is measured by respective angle in each quadrant of circular motion. Due to stick slip motion during velocity reversal generate glitches near zero velocity. Root-mean-square error (RMSE) is calculated based on radial error of circular motion to show variance of errors towards average. The results are experimentally shown that glitches have higher reduction in lower velocity by comparing between applied with and without friction feedforward controller. Better reduction in contour errors improves precision of machine tools and hence increases productivity.